Innovative cathode flow-field design for passive air-cooled polymer electrolyte membrane (PEM) fuel cell stacks - Lee, Jaeseung; Gundu, Mohamed Hassan; Lee, Nammin; Lim, Kisung; Lee, Seung Woo; Jang, Seung Soon; Kim, Jin Young; Ju, Hyunchul (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
A novel cathode flow-field design suitable for a passive air-cooled polymer electrolyte membrane (PEM) fuel cell stack is proposed to enhance the water-retaining capability under excess dry air supply conditions. The innovative cathode flow-field is designed to supply more air to the cooling channels and further enables deceleration of the reactant air in the gas channels and acceleration of the coolant air in the cooling channels simultaneously along the air flow path. Therefore, the design facilitates the waste heat removal through the cooling channels while the water removal by the reactant air is minimized. The conceptual cathode flow-field design is validated using a three-dimensional PEM fuel cell model. The detailed simulation results clearly demonstrate that the new cathode flow-field design exhibits superior water-retaining capability compared with a conventional cathode flow-field design (parallel flow channel configuration) under typical air-cooled fuel cell operating conditions. This study provides a new strategy to design cathode flow-fields to alleviate notorious membrane dehydration and unstable performance issues in a passive air-cooled PEM fuel cell stack. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: WATER TRANSPORT; PERFORMANCE; TEMPERATURE